24.1k views
2 votes
I don't understand this problem and how it equals 1 (attached). I thought if -3 =-x squared it would be 3*3 and then plus 5. I cannot think of a way to make this 1. What am I doing wrong?

I don't understand this problem and how it equals 1 (attached). I thought if -3 =-x-example-1
User Jova
by
5.3k points

1 Answer

0 votes

Answer:

f(2) = 1

f(-3) = 4

Explanation:

We are given the function:


\displaystyle \large{f(x) = - {x}^(2) + 5}

To evaluate the function, substitute the number in.

Evaluate f(2)


\displaystyle \large{f(2) = - {(2)}^(2) + 5} \\ \displaystyle \large{f(2) = - 4+ 5} \\ \displaystyle \large{f(2) = 1}

Evaluate f(-3)


\displaystyle \large{f( - 3) = - {( - 3)}^(2) + 5} \\ \displaystyle \large{f( - 3) = - 9+ 5} \\ \displaystyle \large{f( - 3) = - 4}

User Mayank Bhatnagar
by
4.1k points